Nanoscale constraints on the shock-induced transformation of zircon to reidite - Montalvo, S.; Reddy, Steven; Saxey, David; Rickard, William; Fougerouse, Denis; Quadir, Z.; Johnson, Tim (Elsevier Science BV, 2019)
In a hypervelocity impact event, the temperatures and pressures generated by the shock waves far exceed the values produced by endogenic processes. The shock-induced processes can modify the distribution of trace elements in zircon grains located in target rocks, potentially affecting the geochemical reliability of zircon, but also providing an opportunity to better understand the mechanisms of shock deformation. The formation of reidite lamellae by the shock-induced phase change of zircon has previously been proposed to be a diffusionless, martensitic transformation, with no associated atomic mobility over nanometre length scales. However, nanoscale characterization of the zircon–reidite interface and a low-angle boundary within the reidite by atom probe tomography, transmission electron microscopy and correlative analytical techniques, shows localised enrichment of particular trace elements (Y, Al, Ca, Be, Mg, Mn, and Ti). These observations indicate the presence of additional short-range diffusional components to explain the local compositional variations observed at the nanoscale for the high-pressure transformation of zircon to reidite lamellae. A new model for this transformation is proposed that consists of two stages: 1) the early stage of the impact event where the shock waves induce defects in the zircon grain and trigger a phase transformation, resulting in trace element segregation by interface migration; and 2) the recovery stage where the trace elements and shock induced defects migrate to areas of lower energy.